The influence of exercising at the lactate threshold on the aerobic training response - Wheeler, T. (1997)
The blood lactate response to training adapts to a greater degree than VO2max. This training adaptation is specific to the mode of training. Changes in VO2max. should not be the sole measure of training adaptation. It appears that training to improve the blood lactate response to exercise is the type of training required to improve endurance performance. Some evidence exists to suggest that training above the LT is beneficial, but the optimal training intensity for altering the blood lactate response to exercise is still not known. Periodic re-testing of the blood lactate - exercise intensity relationship is required to continually upgrade the level of training as improvement occurs.